Preoperative skin asepsis in bovine surgery: an outcome-blinded 3-arm randomized clinical trial under non-sterile operating room conditions - Marchionatti, Emma; Constant, Caroline; Steiner, Adrian (Frontiers in Veterinary Science, 2024)
BackgroundSurgical site infections (SSI) following clean abdominal surgery in cattle pose significant economic and welfare concerns. Preoperative skin asepsis aims to minimize microbial load over the surgical field before and throughout surgery to minimize its risk. While chlorhexidine (CHX) and povidone-iodine (PVI) are commonly used antiseptics for this purpose, our study introduces the so far unexplored use of octenidine (OCT) in veterinary surgery.MethodsWe compared in a single-center, prospective, randomized, outcome-blinded, 3-arm trial the effectiveness of an OCT-based protocol to CHX- and PVI-based protocols. Cattle aged 2 years or older, needing a clean standing flank laparotomy (e.g., exploratory laparotomy, right flank omentopexy, left flank abomasopexy), were eligible. Exclusion criteria comprised skin abnormalities, recent antibiotic use, or debilitating conditions with systemic involvement or distant site infections. Patients were randomized 1:1:1 with concealed allocation using unique identifiers. Skin bacterial reduction (immediate [IRF] and delayed [DRF] reduction factors), SSI rate, and wound scores were evaluated. Wound scores were rated on a 0 to 6 scale, considering the presence and severity of discharge and swelling.ResultsOut of 373 assessed cattle, 126 were included and randomized: PVI (n = 42), CHX (n = 41), OCT (n = 43). All protocols significantly reduced bacterial counts, with PVI exhibiting lower IRF. No significant differences were observed in DRF. The summer season and duration of surgical procedures had a negative impact on IRF and DRF in all groups, respectively. Nine of 118 patients (7.6%) with complete follow-up developed SSI. Higher wound scores were associated with development of SSI. Wound scores ≥3 at day 10 postoperatively predicted SSI with high sensitivity and specificity. Microbial flora in SSI included typical skin bacteria and opportunistic pathogens.ConclusionAll protocols met minimum FDA standards in reducing bacterial colonization. While limited by sample size and single-center design, this study confirms the OCT-based protocol as a valuable option for preoperative skin asepsis in clean abdominal bovine surgery.